2017
DOI: 10.47779/ajhs.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Student Embarrassment Toward Condom Purchase/Acquisition

Abstract: While adolescents seem aware of the need for condom use, sexual practices do not always reflectthis awareness. Recent research indicates that sexually active adolescents aged 15-24 acquire half of allnew sexually transmitted infections (STI’s). Often times, condoms are not used due to embarrassment. Assuch, the purpose of this research was to examine the attitude of embarrassment as it relates to condomuse, acquisition, and negotiation. Data were drawn from a sample of 278 college students at a midsizedunivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
2
Order By: Relevance
“…28 However, the finding that men had more embarrassment in negotiation and actual use than women was unexpected. This is inconsistent with previous studies on college student embarrassment about condoms, which found women having higher rates of embarrassment in general 17 and during acquisition, 17,18 but no significant differences between men and women related to negotiation and actual use. 17 There are a few potential reasons for the findings of the current study.…”
Section: Condoms On Campuscontrasting
confidence: 99%
See 3 more Smart Citations
“…28 However, the finding that men had more embarrassment in negotiation and actual use than women was unexpected. This is inconsistent with previous studies on college student embarrassment about condoms, which found women having higher rates of embarrassment in general 17 and during acquisition, 17,18 but no significant differences between men and women related to negotiation and actual use. 17 There are a few potential reasons for the findings of the current study.…”
Section: Condoms On Campuscontrasting
confidence: 99%
“…This is inconsistent with previous studies on college student embarrassment about condoms, which found women having higher rates of embarrassment in general 17 and during acquisition, 17,18 but no significant differences between men and women related to negotiation and actual use. 17 There are a few potential reasons for the findings of the current study. Given that most of the condom use of participants related to male condom use, perhaps men felt an additional burden to be knowledgeable and competent in their use.…”
Section: Condoms On Campuscontrasting
confidence: 99%
See 2 more Smart Citations